Effect of Strain Induced α′ Martensite on Concentration of Hydrogen Around a Crack Tip in Austenitic Stainless Steels: FE Simulation. (2015) - Wang, Y.F.; Dou, D.Y.; Gong, J.M.; Shen, L.M.; Li, X.F.; Jiang, W.C.
Abstract: Compared to the stable austenitic stainless steels (ASSs), the metastable ASSs, e. g. 304L, in which α' martensite forms upon strain, can be severely embrittled by hydrogen. This is because the α′ martensite is inherently more sensitive to hydrogen embrittlement (HE) than γ austenite, and the diffusivity of hydrogen in it is much higher than in γ austenite. It has been frequently observed in metastable ASSs that the α′ martensite formed due to strain is the preferred crack path during HE. And it has been suggested that the α′ martensite can act as "hydrogen diffusion highways" in metastable ASSs, leading to an increased hydrogen concentration at a critical site (such as that ahead of a crack tip) exceeding a certain critical value for crack initiation or growth. However, although many authors have realized this enhance effect of strain-induced α' martensite on diffusion of hydrogen, no document shows that how the hydrogen concentration around a crack tip in metastable ASSs is affected by the strain-induced α' martensite. In this study we used finite element method to analyze the time evolution of hydrogen concentration around a crack tip in 304L ASS considering the combined effect of strain-induced α' martensite and hydrostatic stress on hydrogen diffusion. The results are conducive to further understand the HE phenomenon and mechanism of metastable ASSs, and helpful to establish the method relating the crack initiation and growth acceleration to the time evolution of hydrogen concentration ahead of the crack tip.